Building information modeling (BIM): exploring level of development (LOD) in construction projects - Ahmad Latiffi, Aryani (2015)
Level of Development (LOD) is a protocol exhibit to address the basic guidelines of Building Information Modeling (BIM). The basic guidelines were created to identify specific content requirements, authorize use and purpose. LOD identifies how much information is known about a model at a given time. The use of LOD is to reduce the problems due to inadequate information needed in projects. Therefore, this paper aims to explore the implementation of LOD in projects using BIM in the Malaysian construction industry. In order to do so, a literature review was carried out to identify basic guidelines of the LOD specification. In addition to this, semi-structured interviews were conducted with BIM consultants from the public and private sector. The findings revealed that the implementation of LOD in Malaysia is varied with its own purpose. From the use of LOD, it helps construction players to get the information that they can be used.